Optical element, light source device, image projection device, and method for manufacturing optical element

JP2023166765A5Active Publication Date: 2025-04-07CANON KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022077528
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-05-10
Publication Date
2025-04-07
Estimated Expiration
2042-05-10

AI Technical Summary

Technical Problem

Diffractive optical elements used in high-intensity light sources, such as projectors, suffer from decreased diffraction efficiency due to material deterioration when irradiated with high-intensity light for extended periods, particularly when using siloxane resin materials.

Method used

The optical element is designed with a base material and an optical element portion made of organopolysiloxane, where the atomic concentration ratio of carbon atoms to silicon atoms in specific ranges is controlled to suppress performance deterioration. This is achieved by ensuring the surface side ratio of carbon to silicon atoms is higher than the base material side ratio, and optionally incorporating a coating layer to stabilize the structure.

Benefits of technology

The design effectively maintains high diffraction efficiency even under prolonged exposure to high-intensity light, reducing material degradation and maintaining optical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0001_ABST
    Figure 00000000_0001_ABST
  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide an optical element that prevents a reduction in performance when irradiated with high intensity light for a long time.SOLUTION: An optical element has a substrate, and an optical element part formed of a material including organopolysiloxane as a main component on the substrate. For the optical element, when (C / Si)a is the average value of the atomic concentration ratios of carbon atoms to silicon atoms within a range from 0.5 μm to 3 μm toward the substrate from a surface on the opposite side of a surface of the optical element part in contact with the substrate, and (C / Si)b is the average value of the atomic concentration ratios of carbon atoms to silicon atoms within a range from 0.5 μm to 3 μm toward the inside of an optical element layer from the surface of the optical element part in contact with the substrate, (C / Si)a is larger than (C / Si)b.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an optical element, a light source device, an image projection device, and a method for manufacturing an optical element. [Background technology]

[0002] In recent years, diffractive optical elements have been combined with laser light sources and are being used in parts of electronic devices such as projectors, as described in Patent Document 1. The diffractive optical element described in Patent Document 1 comprises a diffractive optical section having a diffractive structure formed on a light-transmitting substrate made of an inorganic material such as glass. The material constituting the diffractive optical section is preferably heat-resistant and light-resistant, and Patent Document 1 discloses a siloxane-based resin material with a siloxane bond backbone as such a material. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2014-228674 [Overview of the Initiative] [Problems that the invention aims to solve]

[0004] Patent Document 1 specifies, for example, 60 W / cm² as the intensity of light irradiated onto the diffractive optical element. 2 Examples of this have been disclosed. However, even higher intensities, for example, 300 W / cm², have been disclosed. 2 When light of a certain intensity is irradiated for a long period of time, even when a siloxane-based resin material is used for the material constituting the diffractive optical part, as in Patent Document 1, the diffraction efficiency of the diffractive optical element may decrease.

[0005] This invention has been made in view of the above-mentioned problems. Specifically, the purpose of this invention is to provide an optical element that suppresses performance degradation when irradiated with high-intensity light for a long period of time. [Means for solving the problem]

[0006] An optical element according to one aspect of the present invention is an optical member having a substrate and an optical element portion made of a material mainly composed of organopolysiloxane on the substrate, wherein (C / Si)a is the average value of the atomic concentration ratio of carbon atoms to silicon atoms in a range of 0.5 μm to 3 μm toward the substrate from the surface of the optical element portion opposite to the surface in contact with the substrate, and (C / Si)b is the average value of the atomic concentration ratio of carbon atoms to silicon atoms in a range of 0.5 μm to 3 μm toward the optical element portion from the surface in contact with the optical element portion and the substrate, and (C / Si)a is greater than (C / Si)b.

[0007] Furthermore, another embodiment of the present invention relates to a method for manufacturing an optical element, comprising the step of forming an optical element portion on a substrate, wherein the step of forming the optical element portion includes a step of post-processing, and the optical element portion formed after the post-processing is characterized in that, when (C / Si)a is the atomic concentration ratio of carbon atoms to silicon atoms in a range of 0.5 μm to 3 μm toward the substrate from the surface of the optical element portion opposite to the surface in contact with the substrate, and (C / Si)b is the atomic concentration ratio of carbon atoms to silicon atoms in a range of 0.5 μm to 3 μm toward the optical element portion from the surface in contact with the optical element portion and the substrate, (C / Si)a is greater than (C / Si)b. [Effects of the Invention]

[0008] According to the present invention, it is possible to provide an optical element that suppresses performance degradation when irradiated with high-intensity light for a long period of time. [Brief explanation of the drawing]

[0009] [Figure 1] This is an explanatory diagram showing a projector as an image projection device, which is an example of an electronic device equipped with an optical element according to the first embodiment. [Figure 2] This is an explanatory diagram of a light source device having an optical element according to the first embodiment. [Figure 3] (a) is a top view showing the optical element according to the first embodiment, and (b) is a cross-sectional view showing the optical element according to the first embodiment. [Figure 4] Figures (a) to (h) are explanatory diagrams of a method for manufacturing a diffractive optical element according to the first embodiment. [Figure 5] This figure shows the results of surface analysis performed by EDS on the cross-section of the diffractive optical element portion of the optical element according to Example 1. [Figure 6] This figure shows the results of surface analysis performed by EDS on the cross-section of the diffractive optical element portion of the optical element according to Comparative Example 1. [Modes for carrying out the invention]

[0010] Hereinafter, embodiments for carrying out the present invention will be described in detail with reference to the drawings. (First embodiment) Figure 1 is an explanatory diagram showing a projector as an image projection device, which is an example of an electronic device equipped with optical elements according to the first embodiment.

[0011] The projector 500 comprises an optical system 550 for the projector and a control device 530 for controlling the optical system 550. The optical system 550 includes a light source device 501 and a plurality of optical elements (polarization conversion elements 502 to projection lens 511).

[0012] The light source device 501 emits white light 602. The white light 602 consists of red light 602r, green light 602g, and blue light 602b, shown by the dotted line. The red light 602r, green light 602g, and blue light 602b are incident on the polarization conversion element 502 and converted by the polarization conversion element 502 into linearly polarized light with a uniform polarization direction, shown by the solid line, which are red illumination light 604r, green illumination light 604g, and blue illumination light 604b. These red illumination light 604r, green illumination light 604g, and blue illumination light 604b are separated into red illumination light 604r and blue illumination light 604b and green illumination light 604g by the dichroic mirror 503.

[0013] The green illumination light 604g passes through a polarization beam splitter (hereinafter referred to as PBS) 504, which is a polarization separation element, and a phase compensation plate 505g, and reaches a light modulation element 506g. The red illumination light 604r and the blue illumination light 604b pass through a polarizing plate 507 and are incident on a color selectivity phase plate 508. The color selectivity phase plate 508 maintains the polarization direction of the red illumination light 604r while rotating the polarization direction of the blue illumination light 604b by 90°.

[0014] The red illumination light 604r emitted from the color selectivity phase plate 508 passes through PBS 509 and a phase compensation plate 505r and reaches a light modulation element 506r. The blue illumination light 604b emitted from the color selectivity phase plate 508 is reflected by PBS 509, passes through a phase compensation plate 505b, and reaches a light modulation element 506b. Each of the light modulation elements 506r, 506g, 506b is constituted by a reflective liquid crystal panel or a digital micromirror device. Note that a transmissive liquid crystal panel can also be used as the light modulation elements 506r, 506g, 506b.

[0015] The control device 530 controls the light modulation elements 506r, 506g, 506b according to the input image data. Thereby, the light modulation elements 506r, 506g, 506b modulate the incident red illumination light 604r, green illumination light 604g, and blue illumination light 604b, and convert them into red image light 615r, green image light 615g, and blue image light 615b.

[0016] These red image light 615r, green image light 615g, and blue image light 615b are synthesized through PBS 504, 509 and a synthesis prism 510, and are projected onto a projection surface such as a screen by a projection lens 511. Thereby, a color image is displayed as a projection image.

[0017] Figure 2 is an explanatory diagram of a light source device having an optical element according to the first embodiment. The light source device 501 includes a plurality of laser light sources 41, a diffractive optical element 10 as an optical element according to the first embodiment, and a phosphor 43. The diffractive optical element 10 is positioned on the light-emitting side with respect to the plurality of laser light sources 41, and the phosphor 43 is positioned on the light-emitting side with respect to the diffractive optical element 10.

[0018] The laser light source 41 is, for example, a semiconductor laser. Multiple laser light sources 41 may include laser light sources that emit laser light 44 of at least one color from red, green, and blue. It is preferable to include at least a laser light source that emits blue laser light 44 (with a wavelength in the range of, for example, 400 nm to 460 nm). Each laser light source 41 has an output of approximately 300 W / cm². 2 A laser beam 44 with the specified irradiation intensity is emitted. Each laser light source 41 is driven and controlled by the control device 530 shown in Figure 1. If multiple laser light sources 41 include laser light sources that emit red, green, and blue light respectively, the phosphor 43 can be omitted. Since red and green light have less energy than blue light even at the same irradiation intensity, the diffractive optical element 10 irradiated with red or green light may not experience a decrease in diffraction efficiency. In that case, a conventional diffractive optical element can be used for the diffractive optical element 10 irradiated with red or green light.

[0019] Multiple laser light sources 41 are arranged in an array and irradiate the diffractive optical element 10 with laser light 44. The laser light 44 that passes through the diffractive optical element 10 is irradiated onto the phosphor 43. The diffractive optical element 10 has a substrate 12 and a diffractive optical element part 13 as an optical element part on the substrate 12.

[0020] Figure 3(a) is a top view showing the diffractive optical element 10 according to the first embodiment, and Figure 3(b) is an enlarged view of a part of the cross-section of the diffractive optical element 10 according to the first embodiment along the line A-A' in Figure 3(a).

[0021] As described above, the diffractive optical element 10 comprises a substrate 12 and a diffractive optical element portion 13 provided on the substrate 12. The diffractive optical element portion 13 has a diffraction structure 14 on the surface opposite to the surface in contact with the substrate 12, which is an uneven shape for diffracting light.

[0022] The diffractive optical element 10 also further has a flat portion 15 formed integrally with the diffractive optical element portion 13 on the substrate 12 and having a flat surface. In the diffractive optical element 10, multiple diffractive optical element portions 13 are arranged in an array on the substrate 12.

[0023] Each diffractive optical element 13 is irradiated with a circular or elliptical laser beam 44 by a corresponding laser light source 41. The circular or elliptical laser beam 44 irradiated onto each diffractive optical element 13 is focused by the corresponding diffractive optical element 13 onto the phosphor 43 to form a predetermined shape. The predetermined shape is, for example, rectangular. By focusing the laser beam 44 into a rectangular shape to match the shape of the optical modulation elements 506r, 506g, and 506b of a reflective liquid crystal panel, the light can be utilized uniformly and without waste.

[0024] For example, cerium-doped yttrium aluminum oxide (YAG:Ce) can be used as the material for the phosphor 43. A portion of the blue laser light 44 irradiated onto the phosphor 43 is excited and converted into yellow light. This yellow light and the remainder of the blue laser light 44 combine to generate white light 602. The white light 602 emitted from the phosphor 43 as diffused light is converted into parallel light by a collimator lens (not shown), and uniformly distributed light is emitted from the light source device 501.

[0025] The substrate 12 is an inorganic light-transmitting substrate, and is composed of a material that transmits at least blue light, for example, a material that transmits visible light with a wavelength of 380 nm to 780 nm. Preferably, the substrate 12 is composed of a material having sufficient transmittance, specifically 90% or more, so that the irradiated light can be transmitted through it, and glass is used as an example.

[0026] As the glass, inorganic glass containing at least one component selected from the group consisting of zirconium oxide, titanium oxide, tantalum oxide, niobium oxide, hafnium oxide, lanthanum oxide, lithium oxide, gadolinium oxide, silicon oxide, calcium oxide, barium oxide, sodium oxide, potassium oxide, boron oxide, and aluminum oxide can be used.

[0027] As the base material 12, a glass base material formed by grinding, polishing, mold molding, or float molding can be used. To improve the adhesion between the base material 12 and the diffractive optical element portion 13 and the flat portion 15, the strength of the base material 12, and the flatness of the base material 12, the surface of the base material 12 may be cleaned or polished. In addition, an adhesive layer, a hard coat layer, a refractive index adjustment layer, etc., may be provided between the base material 12 and the diffractive optical element portion 13 and the flat portion 15.

[0028] The diffractive optical element portion 13 and the flat portion 15 are made of a material mainly composed of organopolysiloxane. Organopolysiloxane contains siloxane bonds with high bond energy in its main backbone and has high light resistance. Therefore, by making the diffractive optical element portion 13 from a material mainly composed of organopolysiloxane, the degradation of the diffractive optical element portion 13 due to irradiation with light is suppressed. In particular, the intensity of light transmitted through the diffractive optical element portion 13 is 100 W / cm². 2 When the photon energy exceeds a certain limit, or when the light transmitted through the diffractive optical element 13 is high-energy light such as blue light, it is effective to use a material mainly composed of siloxane for the diffractive optical element 13. The organopolysiloxane may be, for example, silicone (silicone rubber, silicone resin).

[0029] Organopolysiloxanes are typically obtained by curing curable silicones. Curable silicones are classified into addition-type silicones and condensation-type silicones based on their curing mechanism, but both can be used. The type of organopolysiloxane can be appropriately selected based on the ease of transferring the shape of the diffraction structure 14 and the ease of controlling the fluidity of the material. Curing methods include heat curing, ultraviolet curing, and moisture curing, but ultraviolet curing is preferred because it allows for uniform curing within the cured product and results in less residual stress within the cured product. With ultraviolet curing, for example, when transferring the shape of the diffraction structure 14 with high precision, it is not necessary to heat the resin before and after the transfer, and the diffraction structure 14 can be formed with high precision.

[0030] Raw materials for forming organopolysiloxanes include organopolysiloxanes having one or more alkenyl groups in the molecule, and organohydrogenpolysiloxanes having one or more silicon-bonded hydrogen atoms in the molecule. Other crosslinkable reactive groups may include radical polymerizable functional groups having ethylenic double bonds, such as vinyl groups, allyl groups, and alkenyl groups like isopropenyl groups, or cationic polymerizable functional groups such as epoxy groups, oxetane groups, alicyclic epoxy groups, and vinyl ether groups. Organopolysiloxanes formed from such raw materials may be linear, have branched structures in part of their molecular structure, or be cyclic. They may also be three-dimensionally crosslinked in a network-like structure.

[0031] The diffractive optical element portion 13 has a distribution in the thickness direction of the ratio of silicon atomic concentration to carbon atomic concentration. Here, the thickness direction is the direction perpendicular to the surface in contact with the substrate 12 and the diffractive optical element portion 13, that is, the direction along the direction of propagation of the laser light 44 incident on the diffractive optical element 10. In the thickness direction of the diffractive optical element portion 13, the average value of the atomic concentration ratio of carbon atoms to silicon atoms in the range of 0.5 μm to 3 μm toward the substrate 12 from the surface of the diffractive optical element portion 13 opposite to the surface in contact with the substrate 12 is defined as the surface-side ratio (C / Si)a. On the other hand, in the thickness direction of the diffractive optical element portion 13, the average value of the atomic concentration ratio of carbon atoms to silicon atoms in the range of 0.5 μm to 3 μm toward the interior of the diffractive optical element portion 13 from the surface in contact with the diffractive optical element portion 13 and the substrate 12 is defined as the substrate-side ratio (C / Si)b. In this embodiment, the diffractive optical element 10 has the characteristic that the surface-side ratio (C / Si)a is greater than the substrate-side ratio (C / Si)b. As a result, approximately 300 W / cm² is emitted from the laser light source 41. 2 Even when irradiated for a long period of time with a laser beam 44 having high intensity, a decrease in the performance of the diffractive optical element 10, that is, a decrease in the diffraction efficiency in the diffractive optical element section 13, can be suppressed. The surface side ratio (C / Si)a is preferably 1.5 times or more the substrate side ratio (C / Si)b.

[0032] The reason why the diffractive optical element 10 according to this embodiment can suppress performance degradation even when irradiated with high-intensity light for a long period of time, due to the above-mentioned features, is thought to be as follows.

[0033] The organopolysiloxane, the main component of the material for the diffractive optical element 13, is three-dimensionally bonded in molecular chains containing siloxane bonds that form the main skeleton of the organopolysiloxane, via polymerization reaction sites where these chains are bonded by polymerization of acrylic groups, epoxy groups, etc. In addition, the material constituting the optical element contains small amounts of low-molecular-weight siloxanes that were not incorporated into the above three-dimensional bonding, such as cyclic siloxanes like hexamethylcyclotrisiloxane and octamethylcyclotetrasiloxane. The main component referred to here is the component that accounts for 80% or more by volume of the material.

[0034] Low molecular weight siloxanes are highly volatile and are present non-uniformly within the diffractive optical element 13 compared to the three-dimensionally bonded siloxane bond chains and polymerization reaction region. Furthermore, the fact that the surface-side ratio (C / Si)a is greater than the substrate-side ratio (C / Si)b for the atomic concentration ratio of carbon atoms to silicon atoms corresponds to a smaller proportion of low molecular weight siloxanes near the surface of the diffractive optical element 13 on the side from which light is emitted. In other words, the polymerization reaction region formed by the polymerization of organic groups of the organopolysiloxane is uniformly distributed within the diffractive optical element 13, and therefore the carbon atoms within the diffractive optical element 13 are also uniformly distributed. On the other hand, low molecular weight siloxanes, which do not contain carbon atoms, have a smaller proportion near the surface of the diffractive optical element 13 on the side from which light is emitted, and as a result, the surface-side ratio (C / Si)a is larger than the substrate-side ratio (C / Si)b.

[0035] In the diffractive optical element 10 according to this embodiment, the amount of highly volatile low-molecular-weight siloxane remaining near the surface of the diffractive optical element portion 13 on the side from which light is emitted is small. This makes it possible to suppress deformation due to volatilization and an increase in refractive index even when irradiated with high-intensity laser light 44 for a long time. This prevents a decrease in diffraction efficiency.

[0036] Furthermore, near the surface of the diffractive optical element 13 that contacts the substrate 12, a relatively large amount of highly fluid low-molecular-weight siloxane remains within the three-dimensional structure of the organopolysiloxane molecular chains. This suppresses the occurrence of cracks due to the release of residual stress and expansion due to heat generation near the surface of the diffractive optical element 13 that contacts the substrate 12 when irradiated with high-intensity laser light 44 for a long period of time. As a result, a decrease in the diffraction efficiency of the diffractive optical element 10 can be suppressed. The effects described above can be obtained to a greater extent if the surface side ratio (C / Si)a is 1.5 times or more than the substrate side ratio (C / Si)b.

[0037] Furthermore, in the diffractive optical element 10 according to this embodiment, the atomic concentration ratio of carbon atoms to silicon atoms in the flat portion 15 in the range of 0.5 μm to 3 μm in the direction toward the substrate 12 from the surface opposite to the surface in contact with the substrate 12 is (C / Si)c. In this case, (C / Si)a is preferably 0.9 times or more and 1.1 times or less of (C / Si)c.

[0038] The flat portion 15 located around the diffractive optical element portion 13, which is irradiated with high-intensity laser light 44 for a long time, has the same composition as the diffractive optical element portion 13. This makes it possible to mitigate changes in surface shape due to thermal expansion when irradiated with high-intensity laser light 44 for a long time. If (C / Si)a is 0.9 times or more than (C / Si)c, changes in surface shape due to the diffractive optical element portion 13 expanding more than the flat portion 15 due to thermal expansion can be suppressed. Also, if (C / Si)a is 1.1 times or less than (C / Si)c, changes in surface shape due to the flat portion 15 expanding more than the diffractive optical element portion 13 due to thermal expansion can be suppressed.

[0039] The thickness of the flat portion 15 can be set considering factors such as ease of molding and the likelihood of crack formation in the material, but it is preferable to set it to be 20 μm or more. By setting the thickness of the flat portion 15 to 20 μm or more, even if low molecular weight siloxane volatilizes on the surface of the diffractive optical element portion 13 from which light is emitted, the occurrence of cracks can be suppressed.

[0040] The atomic concentration ratio of carbon atoms to silicon atoms in the diffractive optical element section 13 and the flat section 15 can be measured by the following method. First, cross-sections of the diffractive optical element section 13 and the flat section 15 are cut out at five locations and magnified with an electron microscope. Next, surface analysis is performed at the five locations using energy dispersive X-ray spectroscopy (EDS). The surface analysis is performed so that information on the entire film can be obtained at each of the five locations. From the intensity values ​​of silicon atoms and carbon atoms detected by the surface analysis in the film thickness direction (direction perpendicular to the substrate 12), the average value of the atomic concentration ratio of carbon atoms to silicon atoms is calculated for a predetermined range in the film thickness direction. The average values ​​obtained at the five locations are further averaged to obtain the atomic concentration ratio of carbon atoms to silicon atoms.

[0041] In this embodiment, the diffractive optical element 10 preferably has a coating layer on the surface of the diffractive optical element portion 13 that emits light. By having a coating layer on the diffractive optical element 10, deformation and an increase in refractive index due to the rapid volatilization of low molecular weight siloxane when irradiated with high-intensity laser light 44 for a long time can be suppressed. When the diffractive optical element 10 has a coating layer, it is preferable that the coating layer is formed to cover not only the diffractive optical element portion 13 but also the flat portion 15 at the same time.

[0042] The coating layer is preferably composed mainly of inorganic oxides or inorganic fluorides. Examples of inorganic oxides include silicon dioxide, titanium dioxide, tantalum oxide, and zirconium oxide. Examples of inorganic fluorides include magnesium fluoride. In particular, since the diffractive optical element portion 13 is made of a material mainly composed of organopolysiloxane, it is preferable that the coating layer contains silicon dioxide, which is compatible with organopolysiloxane, as its main component, from the viewpoint of adhesion between the diffractive optical element portion 13 and the coating layer.

[0043] The coating layer may consist of one layer or multiple layers. Preferably, the thickness of the coating layer is between 40 nm and 500 nm. If the thickness of the coating layer is 40 nm or more, the rapid volatilization of low-molecular-weight siloxane when irradiated with high-intensity laser light 44 for a long period can be effectively suppressed. If the thickness of the coating layer is 500 nm or less, the stress on the coating layer does not become excessive, and deformation of the diffractive optical element 13 when irradiated with high-intensity laser light 44 for a long period can be suppressed.

[0044] Next, an example of a method for manufacturing the diffractive optical element 10 according to the first embodiment will be described. The method for manufacturing the diffractive optical element 10 according to the first embodiment includes the step of forming a diffractive optical element portion 13 as an optical element portion on a substrate 12, and the step of forming the diffractive optical element portion 13 includes a post-processing step. For the diffractive optical element portion 13 formed after post-processing, the atomic concentration ratio of carbon atoms to silicon atoms in the range of 0.5 μm to 3 μm from the surface of the diffractive optical element portion 13 opposite to the surface in contact with the substrate 12 toward the substrate 12 is defined as (C / Si)a. Also, the atomic concentration ratio of carbon atoms to silicon atoms in the range of 0.5 μm to 3 μm from the surface in contact with the diffractive optical element portion 13 toward the interior of the diffractive optical element portion 13 is defined as (C / Si)b. In this case, (C / Si)a is greater than (C / Si)b.

[0045] The step of forming the diffractive optical element portion 13 on the substrate 12 preferably includes the following steps. (1) A step of placing a raw material mainly composed of organopolysiloxane on a base material 12. (2) A step of sandwiching the raw material between the base material 12 and the mold member and applying pressure. (3) A step of curing the raw materials to form a diffractive optical element section 13 made of a material mainly composed of organopolysiloxane. (4) A step of releasing the molded member from the diffractive optical element part 13. (5) A step of performing post-processing on the diffractive optical element section 13.

[0046] Furthermore, the step of forming the diffractive optical element portion 13 on the substrate 12 more preferably includes a step of forming a coating layer on the diffractive optical element portion 13 between the step of (4) releasing the molded member from the diffractive optical element portion 13 and the step of (5) performing post-processing on the diffractive optical element portion 13.

[0047] Figures 4(a) to 4(h) are explanatory diagrams of the manufacturing method of the diffractive optical element 10 according to the first embodiment.

[0048] First, as shown in Figure 4(a), a transfer mold 81 is prepared as a mold member, which includes a surface with a shape corresponding to the diffraction structure 14. For example, quartz can be used as the transfer mold 81. A release agent 82 is applied to the transfer surface of the transfer mold 81 to ensure smooth demolding afterward. For example, a fluorine-based coating agent can be used as the release agent 82.

[0049] Next, as shown in Figure 4(b), a certain amount of raw material 83, mainly composed of organopolysiloxane raw materials, is placed on one side of the substrate 12. When placing the raw material 83, it is preferable to take measures to ensure that no air pockets, such as bubbles, remain in the raw material 83 or between the raw material 83 and the substrate 12.

[0050] Next, as shown in Figure 4(c), the raw material 83 placed on the base material 12 is brought into contact with the transfer surface of the transfer mold 81, and as shown in Figure 4(d), the raw material 83 is sandwiched between the base material 12 and the transfer mold 81 and a pressing force F is applied. At this time, it is preferable to perform the process while, for example, evacuating the system to prevent air pockets from remaining in the raw material 83.

[0051] Next, as shown in Figure 4(e), ultraviolet light (UV) is irradiated onto the pressurized raw material 83 to cure it. The UV light may be irradiated from the substrate 12 side or from the transfer mold 81 side. This forms the cured member 84. After the curing of the cured member 84 has progressed sufficiently, as shown in Figure 4(f), the transfer mold 81 is released from the cured member 84 to form the diffractive optical element portion 13 having the diffractive structure 14 shown in Figure 4(g). After that, as shown in Figure 4(h), a coating layer 16 is formed on the surface of the diffractive optical element portion 13, and then the diffractive optical element portion 13 is post-treated. In this embodiment, it is preferable that the flat portion 15 is also formed integrally with the diffractive optical element portion 13 at the same time. At this time, it is preferable that the coating layer is formed to cover not only the diffractive optical element portion 13 but also the flat portion 15 at the same time, and it is preferable that the post-treatment is also applied to the flat portion at the same time as the diffractive optical element portion 13.

[0052] The post-treatment process can be any process that, after post-treatment, causes (C / Si)a to become greater than (C / Si)b without impairing the performance of the diffractive optical element 13. Examples of post-treatment processes include heating and vacuum drying. By performing these post-treatments on the diffractive optical element 13, low molecular weight siloxane can be volatilized from the side of the diffractive optical element 13 opposite to the side in contact with the substrate 12.

[0053] The post-treatment is preferably a heat treatment because it can effectively volatilize the low molecular weight components. For example, the heat treatment can be performed at a temperature in the range of 100 to 200°C. In particular, the heat treatment as a post-treatment is preferably performed at a temperature of 120°C or higher and for a heating time of 2 hours or more. By applying a heat treatment as a post-treatment to the diffractive optical element portion 13, the low molecular weight siloxane can be uniformly removed in the plane from the side of the diffractive optical element portion 13 opposite to the side in contact with the substrate 12. By uniformly removing the low molecular weight siloxane in the plane from the side of the diffractive optical element portion 13 opposite to the side in contact with the substrate 12, the difference in deformation due to stress and heat generation between the irradiated and unirradiated areas of the laser beam 44 can be reduced, and the occurrence of cracks can be effectively suppressed.

[0054] Furthermore, the post-treatment may be reduced-pressure drying, and specifically, it is preferable to dry under reduced pressure of 50 Pa or less for 2 hours or more. Alternatively, a heated reduced-pressure treatment may be performed as a post-treatment in combination with the above-mentioned heat treatment.

[0055] Although the step of forming the coating layer 16 is described above as occurring before the post-treatment step, it may also occur after the post-treatment step. By performing post-treatment while the diffractive optical element 13 has the coating layer 16, the rapid volatilization of low molecular weight siloxane can be suppressed, and as a result, the occurrence of cracks in the diffractive optical element 13 caused by the rapid volatilization of low molecular weight siloxane can be suppressed. For this reason, it is preferable that the step of forming the coating layer 16 occurs before the post-treatment step.

[0056] The process of forming the coating layer 16 can utilize dry deposition methods such as vapor deposition or sputtering, or wet deposition methods using a coating solution such as spin coating, spray coating, or dip coating. From the viewpoint of the layer's ability to conform to the complex shape of the diffraction structure 14, dry deposition is preferred, and if wet deposition is used, spin coating or spray coating is preferred.

[0057] [Examples] Next, the optical element according to the first embodiment will be further described using examples and comparative examples, but the embodiments for carrying out the present invention are not limited to the specific examples shown below.

[0058] (Example 1) A glass substrate 12 was prepared, and a diffractive optical element portion 13 having a diffractive structure 14 was formed on the surface of the substrate 12 using a siloxane-based UV-curing resin (product name: KER-4000-UV, manufactured by Shin-Etsu Chemical Co., Ltd.). The process for forming the diffractive optical element portion 13 having a diffractive structure 14 is as described with reference to Figures 4(a) to 4(g). In addition, a flat portion 15 was formed around the diffractive optical element portion 13. After that, a coating layer 16 was formed on the diffractive optical element portion 13, followed by post-processing.

[0059] The coating layer 16 was formed using a sputtering method. A silicon oxide film was deposited on the surface of the diffractive optical element 13 using the sputtering method to a layer thickness of 80 nm. Subsequently, as a post-treatment step, the material was heated in a hot air circulating oven heated to 180°C for 96 hours.

[0060] Regarding the diffractive optical element 10 according to Example 1, which was prepared as described above, the wavelength is 455 nm (300 W / cm²). 2 The initial diffraction efficiency when the laser light 44 was transmitted and diffracted, and the diffraction efficiency after 1000 hours of irradiation with the laser light 44 were measured. As a result, the initial diffraction efficiency was 97.5%, and the diffraction efficiency after 1000 hours of irradiation with the laser light 44 was also 97.5%.

[0061] Figure 5 shows the results of surface analysis performed using EDS with an electron microscope on a cross-section of the diffractive optical element portion 13 of the diffractive optical element 10 according to Example 1, which was fabricated as described above. In Figure 5, the distance traveled from the surface of the diffractive optical element portion 13 opposite to the surface in contact with the substrate 12, toward the substrate 12, is shown as the position in the thickness direction.

[0062] As shown in Figure 5, the diffractive optical element 10 according to Example 1 showed a high value for the atomic concentration ratio of carbon atoms to silicon atoms (vertical axis C / Si in Figure 5) on the side of the diffractive optical element portion 13 opposite to the surface in contact with the substrate 12 (the side in contact with the outside air). From the results of surface analysis by EDS, the surface side ratio (C / Si)a and the substrate side ratio (C / Si)b were calculated, and the surface side ratio (C / Si)a was 2.42, and the substrate side ratio (C / Si)b was 1.08. Similarly, surface analysis by EDS was performed on the flat portion 15 that does not have a diffractive structure 14, and (C / Si)c was calculated to be 2.40.

[0063] (Example 2) In Example 2, the optical element was fabricated in the same manner as in Example 1, except that the coating layer 16 was not formed on the diffractive optical element portion 13. Regarding the diffractive optical element 10 according to Example 2, similar to Example 1, when the laser beam 44 with a wavelength of 455 nm (300 W / cm 2 ) was transmitted and diffracted, the initial diffraction efficiency and the diffraction efficiency after irradiating the laser beam 44 for 1000 hours were measured respectively. As a result, the initial diffraction efficiency was 97.1%, and the diffraction efficiency after irradiating the laser beam 44 for 1000 hours was also 97.1%. Also, regarding the diffractive optical element 10 according to Example 2, a cross-section was cut out and surface analysis was performed in the same manner as in Example 1. As a result, the surface-side ratio (C / Si)a was 2.72, the substrate-side ratio (C / Si)b was 1.20, and (C / Si)c was 2.67.

[0064] (Example 3) In Example 3, an optical element was fabricated in the same manner as in Example 1, except that the heating condition in the post-treatment was heating in a hot air circulation oven at 150 °C for 96 hours. Regarding the diffractive optical element 10 according to Example 3, similar to Example 1, when the laser beam 44 with a wavelength of 455 nm (300 W / cm 2 ) was transmitted and diffracted, the initial diffraction efficiency and the diffraction efficiency after irradiating the laser beam for 1000 hours were measured respectively. As a result, the initial diffraction efficiency was 97.4%, and the diffraction efficiency after irradiating the laser beam 44 for 1000 hours was 96.7%. Also, regarding the diffractive optical element 10 according to Example 3, a cross-section was cut out and surface analysis was performed in the same manner as in Example 1. As a result, the surface-side ratio (C / Si)a was 1.62, the substrate-side ratio (C / Si)b was 1.08, and (C / Si)c was 1.59.

[0065] (Example 4) In Example 4, an optical element was fabricated in the same manner as in Example 1, except that the heating condition in the post-treatment was heating in a hot air circulation oven at 150 °C for 24 hours. Regarding the diffractive optical element 10 according to Example 4, similar to Example 1, when the laser beam 44 with a wavelength of 455 nm (300 W / cm 2The initial diffraction efficiency when the laser light 44 was transmitted and diffracted, and the diffraction efficiency after 1000 hours of irradiation with the laser light, were measured. As a result, the initial diffraction efficiency was 96.9%, and the diffraction efficiency after 1000 hours of irradiation with the laser light 44 was 88.4%. Furthermore, a cross-section of the diffractive optical element 10 according to Example 4 was cut out and surface analysis was performed in the same manner as in Example 1. As a result, the surface-side ratio (C / Si)a was 1.31, the substrate-side ratio (C / Si)b was 1.08, and (C / Si)c was 1.33.

[0066] (Comparative Example 1) In Comparative Example 1, an optical element was fabricated in the same manner as in Example 1, except that the formation of the coating layer 16 and post-treatment were omitted. Regarding the diffractive optical element 10 in Comparative Example 1, the wavelength 455 nm (300 W / cm²) was determined in the same manner as in Example 1. 2 The initial diffraction efficiency when laser light was transmitted and diffracted, and the diffraction efficiency after 1000 hours of laser light irradiation were measured. As a result, the initial diffraction efficiency was 97.1%, and the diffraction efficiency after 1000 hours of laser light irradiation was 76.4%.

[0067] Furthermore, a cross-section of the diffractive optical element portion 13 of the diffractive optical element 10 according to Comparative Example 1 was cut out and a surface analysis was performed, similar to Example 1. The results are shown in Figure 6. In Figure 6, the distance traveled from the surface of the diffractive optical element portion 13 opposite to the surface in contact with the substrate 12, toward the substrate 12, is shown as the position in the thickness direction. As shown in Figure 6, the diffractive optical element 10 according to Comparative Example 1 did not show a distribution in the thickness direction for the atomic concentration ratio of carbon atoms to silicon atoms (vertical axis C / Si in Figure 6). From the surface analysis results by EDS, the surface-side ratio (C / Si)a, substrate-side ratio (C / Si)b, and (C / Si)c were calculated. As a result, the surface-side ratio (C / Si)a was 1.08, the substrate-side ratio (C / Si)b was 1.09, and (C / Si)c was 1.08.

[0068] (Comparative Example 2) In Comparative Example 2, the optical element was fabricated in the same manner as in Example 1, except that no post-processing was performed. Regarding the diffractive optical element 10 in Comparative Example 2, the wavelength was 455 nm (300 W / cm²), similar to Example 1. 2 The initial diffraction efficiency when the laser light 44 was transmitted and diffracted, and the diffraction efficiency after 1000 hours of irradiation with the laser light, were measured. As a result, the initial diffraction efficiency was 97.3%, and the diffraction efficiency after 1000 hours of irradiation with the laser light 44 was 81.2%. Furthermore, a cross-section of the diffractive optical element 10 in Comparative Example 2 was cut out and surface analysis was performed in the same manner as in Example 1. As a result, the surface-side ratio (C / Si)a was 1.08, the substrate-side ratio (C / Si)b was 1.09, and (C / Si)c was 1.08.

[0069] (Comparative Example 3) In Comparative Example 3, instead of post-treatment, a wavelength of 455 nm (1200 W / cm) was used. 2 An optical element was fabricated in the same manner as in Example 2, except that the diffractive optical element section 13 was irradiated with the laser light 44 of ) for 200 hours. Regarding the diffractive optical element 10 in Comparative Example 3, the wavelength was 455 nm (300 W / cm²), similar to Example 1. 2 The initial diffraction efficiency when the laser light 44 was transmitted and diffracted, and the diffraction efficiency after 1000 hours of irradiation with the laser light, were measured. As a result, the initial diffraction efficiency was 85.2%, and the diffraction efficiency after 1000 hours of irradiation with the laser light 44 was 74.3%. Furthermore, a cross-section of the diffractive optical element 10 according to Comparative Example 3 was cut out and surface analysis was performed in the same manner as in Example 1. As a result, the surface-side ratio (C / Si)a was 1.83, the substrate-side ratio (C / Si)b was 1.10, and (C / Si)c was 1.08.

[0070] Table 1 summarizes the results obtained for the diffractive optical elements 10 in Examples 1-4 and Comparative Examples 1-3. Regarding diffraction efficiency, a change of 1.0% or less before and after 1000 hours of irradiation with laser light 44 was evaluated as A, a change of more than 1.0% but 10.0% or less was evaluated as B, and a change of more than 10.0% was evaluated as C.

[0071] [Table 1]

[0072] As shown in Table 1, post-processing resulted in the surface-side ratio (C / Si)a of the diffractive optical element 10 being greater than the substrate-side ratio (C / Si)b. As a result, it was confirmed that high diffraction efficiency could be maintained even after irradiation with high-intensity laser light 44 for 1000 hours.

[0073] Furthermore, if the surface ratio (C / Si)a is 1.5 times or more than the substrate ratio (C / Si)b, the change in diffraction efficiency before and after 1000 hours of irradiation with high-intensity laser light 44 is 1.0% or less, demonstrating a high degree of effectiveness in suppressing the decrease in diffraction efficiency.

[0074] On the other hand, in Comparative Example 1, where no coating layer 16 was formed and no post-treatment was performed, the change in diffraction efficiency before and after irradiation with high-intensity laser light 44 for 1000 hours was greater than 10%. Similarly, in Comparative Example 2, where no post-treatment was performed, the change in diffraction efficiency before and after irradiation with laser light 44 for 1000 hours was also greater than 10%. In both Comparative Examples 1 and 2, the substrate-side ratio (C / Si)b was greater than the surface-side ratio (C / Si)a.

[0075] Furthermore, in Comparative Example 3, the change in diffraction efficiency before and after 1000 hours of irradiation with laser light 44 was greater than 10%. In Comparative Example 3, the values ​​for (C / Si)a1 and (C / Si)c differed significantly, with (C / Si)a1 being greater than 1.1 times that of (C / Si)c.

[0076] The optical element according to the present invention can be used in projectors 500, as well as digital cameras, digital video cameras, electronic viewfinders (EVFs), in-vehicle equipment, and head-up displays, etc.

[0077] The disclosure of embodiments of the present invention includes the following configurations and methods. (Composition 1) Substrate and An optical element portion made of a material mainly composed of organopolysiloxane is placed on the substrate, An optical element having, With respect to the optical element portion, when (C / Si)a is defined as the average value of the atomic concentration ratio of carbon atoms to silicon atoms in a range of 0.5 μm to 3 μm toward the substrate from the surface of the optical element portion opposite to the surface in contact with the substrate, and (C / Si)b is defined as the average value of the atomic concentration ratio of carbon atoms to silicon atoms in a range of 0.5 μm to 3 μm toward the optical element portion from the surface in contact with the optical element portion and the substrate, An optical element characterized by (C / Si)a being greater than (C / Si)b. (Configuration 2) The optical element according to configuration 1, wherein the (C / Si)a is 1.5 times or more the (C / Si)b. (Composition 3) The optical element according to configuration 1 or 2, further comprising a coating layer mainly composed of an inorganic oxide or inorganic fluoride on the optical element portion. (Composition 4) The optical element is a diffractive optical element, The optical element portion is a diffractive optical element portion having a diffractive structure, The diffractive optical element further has a flat portion formed integrally with the diffractive optical element portion on the substrate, and having a flat surface. An optical element according to any one of configurations 1 to 3, wherein (C / Si)c is the average value of the atomic concentration ratio of carbon atoms to silicon atoms in the flat portion in the range of 0.5 μm to 3 μm toward the substrate from the surface opposite to the surface in contact with the substrate, and (C / Si)a is 0.9 times or more and 1.1 times or less of (C / Si)c. (Composition 5) It is equipped with multiple laser light sources and diffractive optical elements. The diffractive optical element is positioned on the light-emitting side with respect to the plurality of laser light sources. A light source device characterized in that the diffractive optical element is the diffractive optical element described in configuration 4. (Composition 6) The light source device according to configuration 5, wherein multiple laser light sources have semiconductor lasers. (Composition 7) The light source device according to configuration 5 or 6, wherein the light emitted from multiple laser light sources includes blue light. (Composition 8) The diffractive optical element further comprises a phosphor arranged on the light-emitting side, The light source device according to any one of configurations 5 to 7, wherein the phosphor comprises cerium-doped yttrium aluminum oxide. (Composition 9) An image projection apparatus comprising an optical system and a control device for controlling the optical system, The optical system includes a light source device and a plurality of optical elements. An image projection apparatus characterized in that the light source device is one of the light source devices described in any one of configurations 5 to 8. (Composition 10) The image projection apparatus according to configuration 9, wherein multiple laser light sources have semiconductor lasers. (Composition 11) The image projection apparatus according to configuration 9 or 10, wherein the light emitted from multiple laser light sources includes blue light. (Composition 12) The light source device further comprises a phosphor positioned on the light-emitting side with respect to the diffractive optical element, The image projection apparatus according to any one of the configurations 9 to 11, wherein the phosphor comprises cerium-doped yttrium aluminum oxide. (Composition 13) The optical system separates the light emitted from the light source device via the phosphor into red light, green light, and blue light. The image projection apparatus according to claim 12, wherein the control device generates a color image. (Method 1) A method for manufacturing an optical element, comprising the step of forming an optical element portion containing an organopolysiloxane on a substrate, The step of forming the optical element portion includes a post-processing step, With respect to the optical element portion formed after the above post-processing, when the atomic concentration ratio of carbon atoms to silicon atoms in the range of 0.5 μm to 3 μm toward the substrate from the surface of the optical element portion opposite to the surface in contact with the substrate is (C / Si)a, and the atomic concentration ratio of carbon atoms to silicon atoms in the range of 0.5 μm to 3 μm toward the optical element portion from the surface in contact with the substrate toward the optical element portion is (C / Si)b, A method for manufacturing an optical element, characterized in that (C / Si)a is greater than (C / Si)b. (Method 2) The aforementioned post-treatment is a heat treatment. The method for manufacturing an optical element according to Method 1, wherein the heat treatment is performed under conditions of a temperature of 120°C or higher and a heating time of 2 hours or more. (Method 3) The process of forming the optical element portion is as follows: A step of placing a raw material mainly composed of organopolysiloxane on the aforementioned substrate, A step of sandwiching the raw material between the base material and the mold member and applying pressure, A step of releasing the mold member after the raw materials have hardened, A method for manufacturing an optical element according to method 1 or 2, including the method described above. (Method 4) The method for manufacturing an optical element according to method 3, wherein the step of forming the optical element portion includes a step of forming a coating layer that covers the optical element portion between the step of releasing the raw material from the mold member after curing and the step of performing the post-processing. (Method 5) The method for manufacturing an optical element according to method 4, wherein the coating layer is made of silicon dioxide. [Explanation of symbols]

[0078] 10 Diffractive optical elements 12 Base material 13 Diffractive optical element section 14 Diffraction structure 15 Flat area 16 Covering layer 41 Laser light source 44 Laser light 81 Transfer type 500 projectors 501 Light source device

Claims

1. A substrate; an optical element portion formed on the substrate and made of a material mainly composed of organopolysiloxane; An optical element having Regarding the optical element portion, when an average atomic concentration ratio of carbon atoms to silicon atoms in a range of 0.5 μm to 3 μm from the surface of the optical element portion opposite to the surface in contact with the substrate toward the substrate is defined as (C / Si)a, and an average atomic concentration ratio of carbon atoms to silicon atoms in a range of 0.5 μm to 3 μm from the surface where the optical element portion and the substrate contact toward the inside of the optical element portion is defined as (C / Si)b, An optical element, characterized in that (C / Si)a is greater than (C / Si)b.

2. 2. The optical element according to claim 1, wherein the (C / Si)a is 1.5 times or more the (C / Si)b.

3. The optical element according to claim 1 , further comprising a coating layer on the optical element portion, the coating layer containing an inorganic oxide or an inorganic fluoride as a main component.

4. the optical element is a diffractive optical element, the optical element portion is a diffractive optical element portion having a diffractive structure, the diffractive optical element further includes a flat portion formed integrally with the diffractive optical element portion on the base material and having a flat surface; 2. The optical element according to claim 1, wherein, when an average atomic concentration ratio of carbon atoms to silicon atoms in a range of 0.5 μm to 3 μm from a surface of the flat portion opposite to a surface in contact with the substrate toward the substrate is defined as (C / Si)c, (C / Si)a is 0.9 times or more and 1.1 times or less of (C / Si)c.

5. A light source and a diffractive optical element, the diffractive optical element is disposed on the light output side with respect to the light source, 5. A light source device, wherein the diffractive optical element is the diffractive optical element according to claim 4.

6. A light source device as described in claim 5, wherein the light source has a semiconductor laser.

7. A light source device as described in claim 5, wherein the light emitted from the light source includes blue light.

8. Further, the optical fiber further includes a phosphor disposed on the light output side of the diffractive optical element, The light source device of claim 7 , wherein the phosphor comprises cerium-doped yttrium aluminum oxide.

9. An image projection device comprising an optical system and a control device for controlling the optical system, the optical system includes a light source device and a plurality of optical elements; 6. An image projection device, comprising: a light source device according to claim 5.

10. The image projection device of claim 9, wherein the light source has a semiconductor laser.

11. The image projection device of claim 9, wherein the light emitted from the light source includes blue light.

12. the light source device further includes a phosphor disposed on a light exit side of the diffractive optical element, 12. The image projection device of claim 11, wherein the phosphor comprises cerium-doped yttrium aluminum oxide.

13. the optical system separates the light emitted from the light source device via the phosphor into red light, green light, and blue light; The image projection device of claim 12 , wherein the control device generates a color image.

14. A method for producing an optical element, comprising a step of forming an optical element portion containing an organopolysiloxane on a substrate, the method comprising the steps of: The step of forming the optical element portion includes a step of performing post-processing, For the optical element portion formed through the post-treatment, from the surface of the optical element portion opposite to the surface in contact with the substrate toward the substrate, in a range of 0.5 μm to 3 μm, When the atomic concentration ratio of carbon atoms to silicon atoms is (C / Si)a and the atomic concentration ratio of carbon atoms to silicon atoms in a range of 0.5 μm to 3 μm from the surface where the optical element portion and the base material contact each other toward the inside of the optical element portion is (C / Si)b, A method for producing an optical element, wherein (C / Si)a is greater than (C / Si)b.

15. The post-treatment is a heat treatment, The method for producing an optical element according to claim 14, wherein the heat treatment is carried out under conditions of a temperature of 120° C. or higher and a heating time of 2 hours or longer.

16. The step of forming the optical element portion includes: placing a raw material containing organopolysiloxane as a main component on the substrate; a step of sandwiching and pressing the raw material between the base material and a mold member; A step of releasing the raw material from the mold member after hardening the raw material; The method for producing an optical element according to claim 14 , comprising:

17. 17. The method for manufacturing an optical element according to claim 16, wherein the step of forming the optical element portion includes a step of forming a coating layer that covers the optical element portion between the step of releasing the raw material from the mold member after hardening and the step of performing the post-processing.

18. The method for producing an optical element according to claim 17 , wherein the covering layer is made of silicon oxide.

19. A light source device described in any one of claims 5 to 8, wherein the light source is composed of a plurality of laser light sources.

20. An image projection device as described in any one of claims 9 to 13, wherein the light source is composed of a plurality of laser light sources.